Au pair-strategier i danske familier - privat husarbejder eller maternalistisk mikrostyring - Helle Stenum (The Royal Danish Library, 2010)
Au pair strategies in Danish host families – private domestic worker or maternalistic micro-management The concept of au pair is highly gendered, as it is historically rooted in a mixture of domestic work, family control and cultural education. The au pair system is a managed migration arrangement which has undergone a rather overlooked development in Scandinavia in recent years.In this article the aim is to shed light on rationalities and subjectivities performed in strategies characterizing the relations between au pair employer and employee in the private space of the family household. Based on an empirical study conducted in 2007/2008 including interviews with au pairs and host families in Denmark, the relation between the au pair and the host family is analysed as gendered house work typically organised as a female-to-female relationship between the extra EU, ethnical minoritized, temporary migrant woman and the Danish, ethnical majoritized citizen.